A comprehensive evaluation index system for low-carbon development of power systems in a load-intensive city - Liang, Yi; Dong, Hong; Gao, Yuqun; Hu, Liujun; Gao, Yanna; Lin, Zihan; Zeng, Fanhong; Xu, Yunxia (Frontiers in Energy Research, 2024)
At present, there is a relative lack of study on the comprehensive index system for low carbon development of power systems in load intensive city in China. Firstly, this paper outlined the main challenges faced in the development process of urban power systems, and determined development goals and key indexes, which combined the macro goals and requirements of the construction of new power system with the development characteristics and trends of load intensive urban power systems.Secondly, an comprehensive index system and evaluation method for the low carbon development of power systems would be proposed that took into account the perspectives of safety, efficiency, cleanliness, low-carbon, and flexibility. Finally, the effectiveness of the proposed index system and evaluation method was verified by taking the development of actual power systems in ultra large load intensive city as an example, which providing support for the development decision-making of actual urban power systems construction and transformation.